Effect on cell survival and cytoophidium assembly of the adRP-10-related IMPDH1 missense mutation Asp226Asn - Keppeke, Gerson Dierley; Chang, Chia-Chun; Zhang, Ziheng; Liu, Ji-Long (Frontiers in Cell and Developmental Biology, 2023)
Inosine monophosphate dehydrogenase 1 (IMPDH1) is a critical enzyme in the retina, essential for the correct functioning of photoreceptor cells. Mutations in IMPDH1 have been linked to autosomal dominant retinitis pigmentosa subtype 10 (adRP-10), a genetic eye disorder. Some of these mutations such as the Asp226Asn (D226N) lead to the assembly of large filamentous structures termed cytoophidia. D226N also gives IMPDH1 resistance to feedback inhibition by GDP/GTP. This study aims to emulate the adRP-10 condition with a long-term expression of IMPDH1-D226N in vitro, and explore cytoophidium assembly and cell survival. We also assessed whether the introduction of an additional mutation (Y12C) to disrupt the cytoophidium has an attenuating effect on the toxicity caused by the D226N mutation Expression of IMPDH1-D226N in HEp-2 cells resulted in cytoophidium assembly in ~70% of the cells, but presence of the Y12C mutation disrupted the filaments. Long-term cell survival was significantly affected by the presence of the D226N mutation, with a decrease of ~40% in the cells expressing IMPDH1-D226N when compared to IMPDH1-WT, however survival was significantly recovered in IMPDH1-Y12C/D226N, with only a ~10% decrease when compared to IMPDH1-WT. On the other hand, IMPDH1 expression level in the D226N-positive cells was <30% of that of the IMPDH1-WT-positive cells, and only slightly higher in the Y12C/D226N, suggesting that although cell survival in Y12C/D226N was recovered, higher expression levels of the mutated IMPDH1 was not tolerated by the cells in the long-term. In conclusion, IMPDH1-D226N effect on photoreceptor cells survival may be the result of a sum of problems: nucleotide unbalance plus a toxic long-life cytoophidium, supported by the observation that by introducing Y12C in IMPDH1 the cytoophidium were disrupted and cell survival significantly recovered, but not the sensibility to GDP/GTP regulation, since higher expression levels of IMPDH1-D226N were not tolerated.